An In‐Depth Analysis of the Houston–Galveston Area Council Regional Hazard Mitigation Plan Under the Disaster Mitigation Act of 2000 (DMA2K). Issue 3 (September 2014) - Olonilua, Oluponmile; Ibitayo, Olurominiyi
<x xml:space="preserve">Abstract</x> The Disaster Mitigation Act of 2000 (DMA2K) requires that each local government develop an individual mitigation plan or actively participate in the development of a multi‐jurisdictional plan. Jurisdictions are required to collaborate with neighboring jurisdictions, agencies or departments, businesses, academic institutions, media, and non‐profit organizations. This study is an indepth analysis of a multijurisidictional plan with multiple mitigation action plans (MAPS) to better understand the levels of coordination of activities both during the planning process and inclusion of collaboration in their MAPS. This study also investigated the inclusion of activities for public information and awareness, multiple hazards, evacuation procedures and communities for special considerations. The results of this study show that less than 45 percent of the jurisdictions incorporated collaboration, evacuation, and technological hazards, while less than 10 percent included sheltering, terrorism, and special needs population. Many political jurisdictions with different levels of exposure and vulnerability submitted the same MAPS, which negate the community specific approach of hazard mitigation. Results from HGAC analysis were compared with Charleston County, SC and showed that Charleston included more elements than those in HGAC. This study is a policy‐learning tool, which provides information for review and revision of future plan updates.